2005
DOI: 10.1136/jramc-151-02-02
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences In The Cause Of Low Back Pain In British Soldiers

Abstract: Female soldiers are significantly more likely to suffer low back pain as a result of physical military training, their occupation, or off-duty activities. Sporting activities do not cause low back pain in women to a greater extent than men By demonstrating the scale of the problem and by determining of the cause of injury, it should now be possible to propose methods of effective intervention to reduce injury, implement those interventions and audit effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…22,23 Our results from patients in primary care are in accordance with findings from national and international population surveys studies that found women to be more affected by LBP. [2][3][4][5][6][7][8][9][10] The finding that women had more pain in other parts of the body associated with LBP was also found by others, 2,24 along with the observed higher prevalence of a positive depression score. 2,25 Unlike in a Dutch cohort study, sex was not a significant factor associated with sick leave for LBP.…”
Section: Meaning Of the Results And Comparison With Other Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…22,23 Our results from patients in primary care are in accordance with findings from national and international population surveys studies that found women to be more affected by LBP. [2][3][4][5][6][7][8][9][10] The finding that women had more pain in other parts of the body associated with LBP was also found by others, 2,24 along with the observed higher prevalence of a positive depression score. 2,25 Unlike in a Dutch cohort study, sex was not a significant factor associated with sick leave for LBP.…”
Section: Meaning Of the Results And Comparison With Other Studiessupporting
confidence: 75%
“…6 British female soldiers were more than 2 times more likely to report LBP then male soldiers. 7 Other studies found female sex to be associated with higher disability from LBP [8][9][10] and more days of sickness absence. 11 It is, therefore, conceivable that women have a higher and different utilization of healthcare service for LBP than men.…”
mentioning
confidence: 99%
“…It may be that the high levels of cardiovascular fitness helps to reduce sex-based differences in injury rates. Several researchers have concluded that sex is an independent factor in predicting injury rates (George et al 2012;Strowbridge 2005), but when corrected for fitness this relationship no longer holds true (Bell et al 2000;Blacker et al 2008;Knapik et al 2011a). …”
Section: Sex Differences In Musculoskeletal Injury (Msi) In Physicallmentioning
confidence: 99%
“…Unemployed and married females performing household activities have reported worse LBP [ 28 ]. Strowbridge [ 29 ] reported that females engaged in physical military training experienced more LBP than men, which was not observed in women who played sports. Taylor et al [ 30 ] identified 5,690 patients with degenerative lumbosacral pathologies and reported a greater prevalence of instability, spondylosis, and spinal stenosis among females and of herniated nucleus pulposus among males.…”
Section: Discussionmentioning
confidence: 99%